Methylprenyl and Prenyl Protection for Sulfonamides - Nikitjuka, Anna; Nekrasova, Aleksandra; Jirgensons, Aigars (Synlett, 2015)
2-Methylprenyl (MePre) is an efficient protection for sulfonamides. The acidic cleavage of this group leads to volatile by-products and the product can be obtained in high purity without additional purification. MePre group is resistant to Pd/C-catalysed hydrogenolysis at 1 atm, Suzuki–Miyaura reaction, Ni(0) catalysis conditions and oxidising reagents such as NIS and DDQ. The prenyl (Pre) group can also be used to protect sulfonamides in certain cases; however, the substrate scope is limited due to the side product formation.
Keywords: sulfonamides; protecting groups; allylation; cations; cleavage